Selection against abdominal fat percentage may increase intramuscular fat content in broilers. (2nd March 2016) - Leng, L.; Zhang, H.; Dong, J.Q.; Wang, Z.P.; Zhang, X.Y.; Wang, S.Z.; Cao, Z.P.; Li, Y.M.; Li, H.
Summary: Excessive abdominal fat content (AFC) has negative impacts on feed efficiency and carcass quality. Unlike AFC, intramuscular fat content (IMFC) could be a favourable trait, which has a positive impact on meat quality. To meet consumers' needs, a long‐term goal of broiler breeders is to decrease AFC and improve the IMFC simultaneously. The current study was designed to investigate the relationship between AFC and IMFC and to compare IMFC, including the pectoral major muscle fat content (PIMFC) and intramuscular fat content of leg muscle (LIMFC), between two broiler lines divergently selected for abdominal fat percentage over 17 generations. The results showed that there was a significant difference in PIMFC and LIMFC between the two lines in all five generation populations used. The birds in the lean line had significantly lower AFC but higher PIMFC and LIMFC than the birds in the fat line. We also detected differences in the liver fat content (LFC) between the two lines and the results showed that birds in the fat line had significant higher LFC than birds in the lean line. Our results indicated that a desirable broiler line with higher IMFC but lower AFC could be obtained by genetic selection.